Gelatin–Poly (γ-Glutamic Acid) Hydrogel as a Potential Adhesive for Repair of Intervertebral Disc Annulus Fibrosus: Evaluation of Cytocompatibility and Degradability. Issue 4 (15th February 2021) - Yang, Jui-Jung; Lin, Yu-Yang; Chao, Kuo-Hua; Wang, Jaw-Lin
Abstract : Study Design: An in vitro experimental study testing a Gelatin–poly (γ-glutamic acid) hydrogel for disc repair. Objective: To evaluate the cytocompatibility and degradability of the above mentioned hydrogel for intervertebral disc annular fibrosis (AF) repair. Summary of Background Data: No repair strategies for correcting annular defects in lumbar discectomy have been clinically well recognized. Exogenous supplementation of regenerative materials to fill defects is a minimally invasive way to restore compromised mechanical properties. The injected materials, most commonly gelatin-based materials with cross-linking agents, serve as sealants and as a scaffold for incorporating biomaterials for augmentation. However, cytotoxicity of hydrogel crosslinking agents is of concern in developing viable materials. Methods: This in vitro experimental study evaluated a newly developed gelatin-based hydrogel for intervertebral disc AF repair. Mechanical strength was augmented by γ-PGA, and 1-(3-dimethylaminopropyl)-3-ethyl-carbodiimide hydrochloride (EDC) was used for material crosslinking. Isolated bovine tail intervertebral discs (IVDs) were used to test the hydrogel, and hydrogel surface monolayer AF cell culture was used to investigate efficacy in hydrogel constructs of different EDC concentrations. Cell metabolic activity was evaluated with Alamar blue assay, cell viability assay with live/dead stain, and sulfated glycosaminoglycan (GAG) and double strain DNA were quantified to evaluate proliferation of implanted cells and synthesis of extracellular matrix (ECM) proteins. Results: EDC concentrations from 10 to 40 mM resulted in significant decreases in AF cell proliferation without obvious influence on cell viability. Higher EDC concentrations resulted in decreased percentage of Alamar blue reduction and GAG and DNA concentration, but did not affect GAG/DNA and live–dead ratios. Degradation tests revealed that higher EDC concentrations decreased the hydrogel degradation rate. Conclusion: The developed gelatin–poly (γ-PGA) hydrogel with 20 mM EDC concentration provides an effective gap-filling biomaterial with good cytocompatibility, suggesting substantial promise for use as a sealant for small AF defects. Level of Evidence: N/A Abstract : Gelatin-based hydrogel with 1-(3-dimethylaminopropyl)-3-ethyl-carbodiimide hydrochloride as the cross-linking agent was demonstrated to be a practical gap-filling biomaterial. This newly developed hydrogel manifested good cytocompatibility and sufficient resistance to degradation, which serves as a promising biomaterial for repair of annular fibrosis of intervertebral disc.